The Correlation of Subjective Fatigue, Negligence, Knowledge of Safety Riding and Length of Work on Traffic Accidents of Online Motorcycle Taxis in Sidoarjo - Nala Astari Pramesti; Noeroel Widajati (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: The number of vehicles in Indonesia has increased every year. The number of two-wheeled vehicles in 2016 was 105.150.082 units and increased to 111.988.863 in 2017 and 120.101.047 in 2018. Unfortunately, along with the increase in motorized vehicle users, the rate of traffic accidents that occurred also increased. One of the causes of the high number of traffic accidents in Indonesia is a large number of jobs in the transportation sector, such as online motorcycle taxis. This study aims to identify the factors that cause traffic accidents, including those caused by fatigue, negligence, knowledge of safety riding, and length of work for online motorcycle taxi drivers. Methods: This study is an analytic observational study with a cross-sectional design. The study population consisted of 110 online motorcycle taxi riders who are members of the Sidoarjo-Porong Online Driver Association Basecamp. Sampling was done by using the total sampling technique. The variables studied included subjective fatigue, negligence, knowledge of safety riding, length of work, and two-wheeled online motorcycle taxi traffic accidents. Data analysis was performed using Cramer’s V Correlation Coefficient or Phi Correlation Coefficient. Results: The results showed a significant correlation between subjective fatigue and the incidence of accidents as indicated by a value of r = 0.289. Furthermore, it was found that a weak correlation between negligence and the incidence of accidents with a value of r = 0.211. No correlation was found between knowledge of safe riding and the incidence of accidents marked with a value of r = -0.169. Meanwhile, there is only a weak correlation between the length of work and the incidence of accidents with a value of r = 0.214. Conclusion: Subjective fatigue, neglect, length of work has a correlation with two-wheeled online motorcycle taxi traffic accidents. There is no correlation between knowledge of safety riding with two-wheeled online motorcycle taxi traffic accidents.